2019
DOI: 10.1002/ca.23322
|View full text |Cite
|
Sign up to set email alerts
|

Medial elbow anatomy: A paradigm shift for UCL injury prevention and management

Abstract: To improve the management outcomes and diagnostic accuracy of the ulnar collateral ligament (UCL) injury, the anatomy of the medial side of the elbow joint is necessary to be understood in terms of the periarticular surroundings rather than the specific ligaments. The aim of this study was to anatomically clarify the medial side of the elbow joint in terms of the tendinous structures and joint capsule. We conducted a descriptive anatomical study of 23 embalmed cadaveric elbows. We macroscopically analyzed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…Previous studies have reported that the UCL of the dominant elbow in professional baseball pitchers was thicker than that of the non-dominant elbow and its thickness was associated with increased laxity against valgus stress [20,25]. Recently, Hoshika et al [26] identified that the anterior bundle of the UCL could be interpreted as part of the tendinous complex, which consisted of the tendinous septum (TS) and the FDS muscle. In other words, UCL thickness could be interpreted as the FDS muscle thickness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that the UCL of the dominant elbow in professional baseball pitchers was thicker than that of the non-dominant elbow and its thickness was associated with increased laxity against valgus stress [20,25]. Recently, Hoshika et al [26] identified that the anterior bundle of the UCL could be interpreted as part of the tendinous complex, which consisted of the tendinous septum (TS) and the FDS muscle. In other words, UCL thickness could be interpreted as the FDS muscle thickness.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the FDS muscle of the index finger is located in the superficial layer and that of the middle finger in the deep layer [27]. Hoshika et al [26] also reported that the tendinous complex might be a pathway of the muscular power of the FPMs to the humeroulnar joint. Taking these anatomical concepts into consideration, the FDS muscles of the index and middle fingers may connect with the TS; thus, these fingers could provide more dynamic stability against valgus stress than that of the ring finger via the TS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the FDS muscle of the index finger is located in the superficial layer and that of the middle finger in the deep layer [27]. Hoshika et al [26] also reported that the tendinous complex might be a pathway of the muscular power of the FPMs to the humeroulnar joint.…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides clinically relevant information that can be used in the development of a program to prevent UCL injury. Recently, there has been a focus on hand muscle training to prevent throwing injuries as well as to improve performance in generating ball velocity [14,26,28]. However, the Thrower's Ten, which has a long history of use by overhead throwing athletes, incorporates multiple strengthening exercises for the shoulder, elbow, and wrist, but fails to address the finger flexors [15].…”
Section: Discussionmentioning
confidence: 99%